Condition monitoring of spur and helical gears using acoustic emission (AE) technology - Raja, Hamzah R. I. (Cranfield University, 2008)
Condition Based Maintenance (CBM) philosophy has become widely accepted by most industries today as a key element in reducing operating cost, and increasing safety and life cycle costs within a environmentally friendly umbrella. One of the important keys to successful CBM is condition monitoring. The investigation reported in this thesis is centred on the application of Acoustic Emissions (AE) technology for condition monitoring of the operational spur and helical gears. Since the application of AE in gear condition monitoring is still under development, understanding the main source of AE during spur and helical gear mesh and the influence of operating parameters on the generation of AE activity is essential. The surface fatigue life of the gears is very much dependent on the specific lm thickness (Ä) value, which is a ratio of oil lm thickness (h) over the composite surface roughness (cms) of the meshing surfaces, during their operations. Thus, the aim of this research programme is to investigate and understand the influence of specific lm thickness (Ä) on the generation of AE activity during spur and helical gear mesh under various operating conditions. A series of experimental investigations were undertaken and these showed that changes in load, speed, temperature, surface roughness and lubricant viscosity influenced the generation of AE. Findings from the tests strongly suggest that asperity contact is the main source of AE during spur and helical gear mesh. In addition, the meshing mechanisms of spur and helical gears are shown to contribute distinct characteristics of AE. Finally, the correlation between specific lm thickness (Ä) and AE r.m.s. established from the investigation, shows the potential of AE technology to monitor lubrication regimes of operational spur and helical gears. This extends the potential of AE technology not only to detect incipient failures during gear operation but also to prevent failure from occurring. With knowledge of the lubrication regime, gear failure associated with wear could be eliminated or reduced and thus increase the reliability of the gears during their operation. i It is concluded that the experimental findings of this research programme will form the foundations for significant advancement in the application of AE to identify the lubrication regime within a gearbox, thereby ensuring optimal conditions for prolonged life. This research has contributed to the condition monitoring community by: 1. 2. 3. 4. Presenting the main source of AE during helical and spur gear mesh. Establishing the correlation between specific lm thickness (Ä) and AE activity during helical and spur gear mesh under various lubrication regimes. Extending the potential of AE technology not only to detect gear incipient failures but to prevent failure from occurring. Forming the foundations for significant advancement in the AE technology to identify the lubrication regime during helical and spur gear operations, thereby ensuring optimal conditions for prolonged life. Several papers presenting the findings of this research have been published in international journals and given at conferences.